COVID-19 as a Catalyst for Innovation: Pharmaceutical Industry Manufacturing Techniques and Management of Endemic Diseases - Anirudh Mehta; Varun Choudhary (International Journal of Multidisciplinary Sciences and Arts, 2023)
The lockdown measures of the Covid-19 pandemic have significantly impacted change in pharmaceutical manufacturing technology, regulation and global supply chains. To respond to unprecedented global demand, significant advances took place and these include platform-based manufacturing such as mRNA and viral vector vaccines, shift to continuous manufacture. Indeed, reducing harm to the buying public through the preservation of product safety and quality, the regulatory modifications such as the EUAs and concurrent process validation accelerated the approvals of vaccines. To achieve the effective knowledge transfer for collaboration like COVAX, the fair distribution of vaccinations for every country in the world was ensured. The fact is that all these concerns will be crucial for maintaining the preparedness for other future health threats in case the pandemic turns into the endemic phase. If the pharmaceutical sector is to make greater investments in scalable production technology, regional manufacturing events and unified regulations they will be in a position to respond to new public health threats in a more efficient manner. In this abstract, the author discusses the lessons learned and their relevance in future global threats and emphasizes the transformative nature of COVID-19 in the generation of pharmacy manufacture.